A Mecke-type characterization of the Dirichlet–Ferguson measure - Eugene Lytvynov (Electronic Communications in Probability, 2023)
We prove a characterization of the Dirichlet–Ferguson measure over an arbitrary finite diffuse measure space. We provide an interpretation of this haracterization in analogy with the Mecke identity for Poisson point processes.